Attention training normalises combat-related post-traumatic stress disorder effects on emotional Stroop performance using lexically matched word lists. Issue 8 (16th November 2016) - Khanna, Maya M.; Badura-Brack, Amy S.; McDermott, Timothy J.; Shepherd, Alex; Heinrichs-Graham, Elizabeth; Pine, Daniel S.; Bar-Haim, Yair; Wilson, Tony W.
ABSTRACT: We examined two groups of combat veterans, one with post-traumatic stress disorder (PTSD) ( n  = 27) and another without PTSD ( n  = 16), using an emotional Stroop task (EST) with word lists matched across a series of lexical variables (e.g. length, frequency, neighbourhood size, etc.). Participants with PTSD exhibited a strong EST effect (longer colour-naming latencies for combat-relevant words as compared to neutral words). Veterans without PTSD produced no such effect, t  < .918, p  > .37. Participants with PTSD then completed eight sessions of attention training (Attention Control Training or Attention Bias Modification Training) with a dot-probe task utilising threatening and neutral faces. After training, participants—especially those undergoing Attention Control Training—no longer produced longer colour-naming latencies for combat-related words as compared to other words, indicating normalised attention allocation processes after treatment.